Toward Safer GI Endoscopy With a Novel Robot-Assisted Endoscopic System - Feng, Guang; Wang, Sai; Li, Jinhua; Zuo, Siyang (IEEE robotics and automation letters, 2024)
Increased demand for minimally invasive surgery has accelerated the adoption of natural orifice transluminal endoscopic surgery. Meanwhile, the increasing complexity of endoscopic procedures has raised the demand for endoscopist competence. In this paper, we present a novel endoscopic system to perform robotic intervention with a flexible endoscope to enhance the safety and efficiency of endoscopy. The system is composed of an endoscopic manipulation module (EMM) for control of endoscopic interventions, a 6 DOFs robotic arm for adjusting the pose of EMM, and a haptic interface for telecontrol. The compact system enables endoscopists to remotely and stably operate flexible endoscopes with one hand. Leader-follower control strategy with active constraint is proposed to guide the motion of the flexible endoscope within the safe working space. The proposed system is validated by recruiting subjects to perform target area localization and endoscopic examinations through highly realistic upper digestive tract phantom. The system can reduce the time of target area localization by at least 10% compared to manual control. The mean angle error can be reduced by 75% with the help of the constraint force. Results demonstrate the potential clinical value of the system in efficient operation and safety control.